Regulatory Impact Assessment in Post-Soviet Countries: Results, Problems and Prospects - I. D. Turgel; A. Zh. Panzabekova (Управленческие науки, 2018)
The subject of research is the institute of regulatory impact assessment, implemented in the sphere of state regulation of economy in post-Soviet countries. The research aims to analyze the main approaches to the implementation of the regulatory impact assessment in the post-Soviet countries — Russia, Armenia, Belarus, Kazakhstan, Kyrgyzstan, Uzbekistan, as well as to determine the prospects of development of this institute in the countries included in the analyzed set. Using the methodology of comparative research, the study collates the concept content of “regulatory impact assessment” in some of the post-soviet countries, the structure of the objects of assessment and government levels, at which it is performed. The research analyzes the methodological framework of the regulatory impact assessment and models of the organization of monitoring and quality control of regulatory impact assessment in the countries from the analyzed set. The paper characterizes the role of the regulatory impact assessment in the system of state regulation of economy in the countries of post-Soviet space, identifies the general and specific features in the functioning of the mechanisms of regulatory impact assessment in the analyzed countries, describes the problems of assessment in the activities of state authorities and local selfgovernment, and substantiates the development prospects of the institute of the regulatory impact assessment. The research provides findings on the need for improving the quality of the existing methodological support of the regulatory impact assessment, the lack of methodical approaches to evaluating the effectiveness of this institution, the risks of formalizing procedures of the regulatory impact assessment, and the feasibility of the regulatory impact assessment “integration” in the national strategy to encourage business and economic growth. Moreover, the paper notes that at the present stage of the development of the regulatory impact assessment institute little attention is paid to finding alternative solutions which require government interference in the economy.